The Mosquito Repellent Activity of the Active Component of Air Freshener Gel from Java Citronella Oil (Cymbopogon winterianus) - Willy Tirza Eden; Dante Alighiri; Kasmadi Imam Supardi; Edy Cahyono (Journal of Parasitology Research)
This study examines the active component of Cymbopogon winterianus (Java citronella) oil, as a green mosquito repellent, obtained through a steam distillation method. Java citronella oil, which contains citronellol, citronellal, and geraniol, was isolated by batch vacuum fractional distillation, and their effect was tested against the dengue fever (DF) vector, known as Aedes aegypti. Furthermore, air freshener gels were formulated with Java citronella oil, carrageenan, gum, sodium benzoate, ethylene glycol, polysorbate 20, sodium chloride, and distilled water, at varying concentrations. The results show that formula I has the best controlled release evaporation for citronellal, citronellol, and geraniol, as well as the best storage time of 16.82 days and 12.77 days for geraniol and citronellol, respectively. The most significant specific gravity (0.0136) was recorded in formula V, while gel formula I exhibited the highest level of instability at 35°C, with a syneresis value of 77.11% in t=72 h and pH 5.33. In addition, formula IV at 5°C demonstrated the highest syneresis (75.34%) in t=72 h, with pH 7.04, while a peak viscosity of 100,958 cP was recorded in formula IV. The repellent activity of each active component was measured based on the period of protection conferred against the bites of Aedes aegypti within one hour, and the results showed geraniol and citronellol, with respective activity of 78.00%±4.83 and 77.34%±3.57, as the most effective.